Inhibition of the quadriceps muscles in elite male volleyball players - Huber, A.; Suter, E.; Herzog, W. (Journal of Sports Sciences, 1998)
Inhibition of the quadriceps muscles was assessed in 13 elite male volleyball players using the interpolated twitch technique. This technique involves applying an electrical stimulus to the voluntarily contracted quadriceps muscles to estimate the number of motor units not fully activated during the contraction. Knee extensor moments and muscle inhibition were measured during isometric contractions at knee angles of 30° and 60° from full extension. A medical history of knee joint injury and pain experienced in the knee during testing were assessed. Previous knee joint injury did not affect the knee extensor moments, but produced a difference in muscle inhibition: muscle inhibition in legs with previous injuries was significantly lower than muscle inhibition in legs with no previous injury. Moderate pain in the knee during testing did not affect muscle inhibition, but was associated with reduced knee extensor moments. We consider that the loss in knee extensor moments associated with pain might be caused by atrophy of the quadriceps muscles as a consequence of the disrupted training routine. The lower muscle inhibition in volleyball players with previous injury suggested that the intense rehabilitation programme that these athletes undergo after knee injury improves muscle activation. As a result, athletes with previous knee joint injuries were able to produce the same knee extensor moments as athletes with no previous injury, probably because of their ability to recruit the available motor units more completely. This recruitment may compensate for the possible loss in muscle mass encountered during the period of injury and detraining.